Dorsal venous complex ligation‐free and parietal endopelvic fascia preserving in laparoscopic radical prostatectomy: A prospective study of single centre - Zhong‐Hua Yang; Yong‐Zhi Wang; Tao Liu; Hang Zheng; Xing‐Huan Wang (BJUI Compass)
Abstract Objectives This study aims to describe a novel dorsal venous complex (DVC) ligation‐free and parietal endopelvic fascia preserving technique for laparoscopic radical prostatectomy and to evaluate its post‐operative outcomes. Methods From April 2020 to May 2021, a total of 125 patients with localized prostate cancer received laparoscopic radical prostatectomy by a single surgeon. In the procedure, a novel technique of DVC ligation‐free and parietal endopelvic fascia preserving was used. Preoperative characteristics of patients and perioperative results were recorded. In this study, continence was defined as zero to one pad per day. Oncological outcomes were evaluated based on positive surgical margin. Results Five patients required a blood transfusion. Mean post‐operative hospital stay was 3.9 days (2–5), and the catheter could be removed on post‐operative day 7 to 9. Final pathologic evaluations were 87 stage pT2, 22 stage pT3a, and 7 pT3b, 9 stage pT4, respectively. The positive surgical margin rate was 10.4% in total. Ninety‐three patients (74.4%) returned to urinary continence 2 months post‐operatively, and 11 patients (11/125) developed biochemical recurrence 6 months post‐operatively. Conclusions The DVC ligation‐free and parietal endopelvic fascia preserving technique provides early recovery from incontinence without adversely affecting the oncological outcome.